Synthesis of Cu/CuO nanostructures - Kenzhina, I.E.; Kozlovskiy, A.L.; Petrov, A.V.; Kadyrzhanov, K.K. (Хабаршы. Физика сериясы, 2018)
Among the variety of synthesized nanostructures, a special place is occupied by Cu nanotubes, due to their physical-chemical and electrical properties, and also because of potential applications in microelectronics. In this paper, we present the results of studies of copper nanostructures synthesis in the form of hollow nanotubes obtained by electrochemical deposition in pores of template matrices based on polymer matrices at polyethylene terephthalate. Electrochemical synthesis in tracks of the template was carried out in potentiostatic mode at a voltage of 0.5 to 1.5 V. By controlling the deposition time, the difference in the applied potentials, the electrolyte temperature, we can change the geometric parameters of synthesized nanostructures. The electrolyte temperature was 25 - 50 °C. Morphology, crystal structure, element and phase composition of nanostructures were studied using the methods of scanning electron microscopy, energy dispersive and X-ray phase analysis. Dependences of the change in structural and conductive properties of synthesized nanostructures from the synthesis conditions are established. Optimal conditions for the synthesis of Cu/CuO nanostructures of various geometries (nanowires and nanotubes) that have potential applications in microelectronics are determined.